Analysis of International Conflicts in Global Politics - Roxana Maria, Toma-Ciobanu (Acta Universitatis Danubius. Relationes Internationales, 2024)
This article explores the complex dynamics of international conflicts in contemporary global politics, analyzing the economic, political, ethnic, and geopolitical factors that contribute to the outbreak and escalation of these conflicts. In a global context marked by economic interdependence and geopolitical shifts, such as the rise of regional powers like China and Russia, international conflicts are no longer confined to traditional state rivalries but are amplified by non-state actors and emerging technologies, such as drones and cyberattacks. The article highlights the crucial role of international organizations, such as the UN and NATO, in managing and resolving conflicts, but also underscores the limitations of these structures in the face of asymmetric conflicts or hybrid wars. It examines how economic sanctions, energy crises, and forced migration affect not only the directly involved states but also global stability. The main conclusion of the research is that a more flexible and multidimensional approach, based on preventive diplomacy, economic development, and international cooperation, is essential for preventing and effectively managing international conflicts in the rapidly changing global order. The analysis offers new perspectives on how international conflicts can be understood and addressed, emphasizing the interaction between deep-rooted causes and recent developments in the technological and geopolitical spheres.